Development and prototyping of a takraw ball feeder for accuracy training based system - Mohamad Syafiq, Mohd Nazaruddin (2008)
The development of electronic and automation in sport is well demanded to improve the training method. Ball feeder is one type of sport training equipment that is used for accuracy training purpose. Unfortunately, there is no automation equipment that had been developed for Sepak Takraw. Therefore, this work is published for the development and prototyping of takraw ball feeder for Sepak Takraw training purposes. This ball feeder used a gravity punching concept where it consists of a rotating arm that is moved by a driver connected to a power window motor to a certain position before the arm is release. The takraw ball feeder is capable to control the launching period of the ball where it is controlled by a controlling unit. This ball feeder invention will make Sepak Takraw training more effective than the current training method.